What Should Economists Know About the Cloud? A Literature Review on Digital Economics - Enxhi Leka (International Telecommunications Society (ITS), 2022)
The climate of technological innovation has presented the world with many solutions, but at the same time, many issues follow. This paper discusses several elements of the backbone network and data centers to encourage researchers to work on this subject and dig deeper into the economic impact, regulation, competition, etc. This paper should be read as a simple guide to this complex industry.
Keywords: 330; Cloud Technologies; Data Center Localization; Data Storage and Computing; Personal Data